Online tuning control for a switch-sharing based multilevel inverter using capacitor voltage balancing / Zalifah Ramli - Zalifah , Ramli (2022)
In these modern days, energy sustainability has gained increasing attention, bringing about the reinforcement of numerous attempts to utilize renewable energy and improve energy efficiency. In relation to this, multilevel inverters, which come from a family of power electronic converters, have a great potential to play an important role in contributing to this field. One type of multilevel inverter which has the potential to perform the task is the switch-sharing-based multilevel inverter. The switch-sharingbased multilevel inverter offers several benefits, such as decreasing the complexity of a circuit, minimizing power losses and contributing to smaller filter size. However, just like diode-clamped multilevel inverter, the switch-sharing-based multilevel inverter also suffers from the unbalanced capacitor voltage issue. This phenomenon degrades the voltage waveforms for the AC-side, which results in an unfavorable operation of the inverter. Therefore, this research adopts the approach of implementing a capacitor voltage balancing circuit based on a buck-boost converter in a five-level switch-sharing-based multilevel inverter topology. For this approach, a performance-based online tuning control based on proportional-integral (PI) configuration is proposed to balance and maintain the capacitor voltages at the desired levels and improve the dynamic performance. Through MATLAB/SIMULINK simulation, a detailed analysis of the results for the buck-boost converter with the proposed online controller with performance-based tuning has been made. For validation purposes, the buck-boost converter has been constructed in the laboratory, and the controller has been implemented on a digital signal processor (DSP). The test conducted with an experimental five-level switch-sharing-based multilevel inverter reveals that satisfactory results have been achieved. Simulation and experimental results reveal that the capacitor voltages can be balanced at high modulation indexes with improved current harmonic performance able to be acquired at the inverter’s output.